THE CORRELATION OF PARENTING STYLE WITH UNDERGRADUATE MEDICAL STUDENTS’ ACADEMIC INTEGRITY IN A MEDICAL SCHOOL - Puspa Maharani; Hikmah Muktamiroh; Lasma Nurhayati (Jurnal Pendidikan Kedokteran Indonesia, 2018)
Background: Academic integrity is one of the main principle in academic culture. Academic integrity, defined as obedience to the principle in academic sphere. However, violation to the academic principle is a common phenomenon occurred in the high education. Integrated academic is closely related to morality, while morality is highly influenced by the parenting method. This study aimed to find relationship between parenting method and academic integrity behavior of student in academic stage of Medical Faculty.